A new technique in reducing self-power consumption in the controller of off-grid solar home system - Mohammad Shariful Islam; Siti Zaliha Mohammad Noor; Hasmaini Mohamad; Nur Ashida Salim; Zuhaila Mat Yasin (Institute of Advanced Engineering and Science, 2022)
Reducing the self-power consumption of an off-grid solar home system is an economic model in which consumer employs photovoltaic (PV) system for its own electrical requirements. The latch-based clock gating approach has been employed in existing solar charge controllers to reduce integrated circuit (IC) power being used in the low-powered intended mode, although the reducing power is limited. This paper presents a self-power reduction technique based on wake-up power and latch-hold time; which minimize power supply during idle time for a solar home system. Wake-up power introduces a push-switch mechanism using typical transistor technology. Latch-hold time function is designed using an operational amplifier and negative-positive-negative (NPN) transistor. A technique with dynamic self-supply mechanism is also introduced for decreasing self-power consumption. The self-power consumption is identified via simulation studies where the result shows that the power usage is 70% lower than traditional approaches. This is determined using a simulated wave-shape analysis.